FDG-PET/CT appearance of injected silicone particles (VOX Implants®) in head and neck tissues - Piccinini, Alessia; Alicandri-Ciufelli, Matteo; Ghidini, Angelo; Bergamini, Giuseppe; Vincenti, Vincenzo; Bacciu, Andrea; Ferri, Teore; Cesinaro, Anna Maria; Presutti, Livio (Acta Biomedica Atenei Parmensis, 2015)
Objetives: In head and neck surgery, Positron Emission Tomography/Computed Tomography imaging (FDG-PET/CT) is often used to identify primary tumor site in patients with unknown primary carcinoma, to predict response after chemoradiotherapy and in some cases, to detect recurrence. To rehabilitate swallowing after surgery in patients with persistent dysphagia, an injectable suspension of silicone (VOX® Implants) can be used to reduce the gaps in the neoglottis. The purpose of this report is to document the PET appearance of PDMS in a series of 3 patients who underwent partial laryngectomy  with subsequent VOX® Implants injection.Material and methods: a retrospective chart and imaging review was performed at our institution. Three patients were identified and included in the study. Appearance of PDMS at PET was described and discussed.Results: An increased uptake of 2-fluoro-2-deoxy-d-glucose (FDG) was noticed at PET in all patientsConclusions: the increased uptake was possibly due to active inflammatory reactions that are necessary for tissue integration of textured silicone particles.